Sistem Informasi Penanganan Komplain di PT. Tebar Digital Kreasi Dengan Metode Scrumban - Ita Wijayanti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The significant influence on human life is caused by the rapid development of technology, which is then utilized in various sectors including the business sector of the provider of goods and services. PT. Tebar Digital Kreasi as an application and website development company with experience in managing projects in an agile manner, clients often complain to get support regarding the problems they are experiencing. Procedures that are still manual in handling complaints make complaint services less than optimal. Complaints that are not resolved within the time specified by management can be a threat to the company. So it can be realized that the handling of complaints is something that must be considered. This study uses the Scrumban method by generating information on complaints that have been handled and have not been handled and reports on the results of complaint handling based on a certain time unit. The results of the research show that it has succeeded in building a complaint handling information system that can assist the Admin in managing client complaints. Test result black box shows that the system is running well and in accordance with expectations with a level of functionality of 100%.